Metadiscourse in web-mediated health communication - Diani, Giuliana (Wydawnictwo Uniwersytetu Jana Kochanowskiego w Kielcach, 2019)

Research article abstracts in English and Italian:Generic and cross-linguistic variationover the last 20 years - Diani, Giuliana (Jan Kochanowski University Press)
The paper examines comparatively and diachronically the generic structure of research article abstracts written in English for international scientific journals and abstracts written in Italian and published in Italian journals in the field of linguistics, with the aim of exploring generic and cross-linguistic variation over the last 20 years. The data consist of two small corpora of English and Italian linguistics research article abstracts spaced at ten-year intervals, namely 1997, 2007 and 2017. The analysis shows that the generic structure and rhetorical organisation of abstracts written in Italian conforms to the international conventions based on the norms of the English academic discourse community. However, they are rhetorically less complex than English abstracts. Diachronic variation has also been observed in the frequency and distribution of every single move across the two language corpora over the decades.

“Hello, my name is Coronavirus”: Popularizing COVID-19 for children and teenagers - Denti, Olga; Diani, Giuliana (Jan Kochanowski University Press, 2022)
The aim of this paper is to examine the popularization strategies adopted in texts destined for children and teenagers which deal with COVID-19. It is well documented that the age and the cognitive profile of the target reader have a strong bearing on the structure and nature of a text (Bruti this volume) and that popularization strategies are adjusted in different ways (Turnbull 2015). As Kolucki and Lemish (2011) emphasize, there is a need for communication with children in a way that is age-appropriate and suitable to their needs and interests. Following this research strand, in this paper we analyze the popularization strategies associated with the explanation of coronavirus in relation to the age of the addressee. To this purpose we focus on English booklets and websites dealing with COVID-19 which address two different age groups, children and teenagers. Attention is paid to examples that highlight popularization strategies on the basis of their verbal and visual elements. The basic methodological framework of this study is discourse analysis, with reliance on notions taken from multimodality (Bateman 2014; Kress – van Leeuwen 2020). This provides instruments suitable for identifying cases where the visual mode interacts with the verbal mode to support popularization strategies.